Exchange Rate Management: The Role of Target Zones - Williamson, John (American Economic Review, 1987)
The essence of the regime of unmanaged floating that prevailed among the major currencies from March 1973 until the Plaza Agreement in 1985 was that the exchange rate was treated as a residual in the process of macroeconomic policy determination. Admittedly there were occasions-such as October 1976 in the case of the pound sterling and October 1978 in the cases of both the U.S. dollar and the Swiss franc-when particular countries became so concerned with a misalignment of their currency that they were forced to abandon benign (or malign) neglect, but such incidents were episodic. Views about a proper or desirable level of the exchange rate played no systematic role in policy formulation. Section I explains why I judge the performance of unmanaged floating to have been unsatisfactory. Section II lists the real social benefits that exchange rate flexibility can afford, which should be preserved by any reformed system. Section III describes the target zone proposal and explains why it would preserve the real benefits of flexibility while overcoming the weaknesses of unmanaged floating. Section IV sketches a possible set of comprehensive principles for policy coordination of which target zones would be one natural element.